Lipidomics Analysis of Behavioral Variant Frontotemporal Dementia: A Scope for Biomarker Development - Kim, Woojin Scott; Jary, Eve; Pickford, Russell; He, Ying; Ahmed, Rebekah M.; Piguet, Olivier; Hodges, John R.; Halliday, Glenda M. (Frontiers in Neurology, 2018)
Behavioral variant frontotemporal dementia (bvFTD) is the most prevalent form of FTD syndromes. bvFTD is characterized clinically by changes in behavior and cognition and pathologically by focal brain atrophy and concomitant loss of lipids. bvFTD is further characterized by eating abnormalities that result in dyslipidemia. Although dyslipidemia is apparent in bvFTD, very little is known about global lipid changes in bvFTD and lipid dysregulation underlying bvFTD. Here, we undertook a comprehensive lipidomics analysis of blood plasma from patients with bvFTD, patients with Alzheimer’s disease (AD) and controls, using liquid chromatography-tandem mass spectrometry, with the aim of understanding lipid dysregulation in bvFTD. In our analysis, we detected all four major classes of lipids (glycerolipids, phospholipids, sphingolipids, sterols), 17 subclasses of lipids, and 3,225 putative individual lipid species in total, as well as a group of dietary lipids. We found that the levels of numerous lipid species were significantly altered in bvFTD compared to AD and control. We found that the total abundance of triglyceride (TG) increased significantly in bvFTD, whereas phosphatidylserine and phosphatidylglycerol decreased significantly in bvFTD. These results suggest manifestation of hypertriglyceridemia and hypoalphalipoproteinemia in bvFTD. We also identified five lipid molecules—TG (16:0/16:0/16:0), diglyceride (18:1/22:0), phosphatidylcholine (32:0), phosphatidylserine (41:5), and sphingomyelin (36:4)—that could potentially be used for developing biomarkers for bvFTD. Furthermore, an analysis of plant lipids revealed significant decreases in monogalactosyldiacylglycerol and sitosteryl ester in bvFTD, indicating altered eating behavior in bvFTD. This study represents the first lipidomics analysis of bvFTD and has provided new insights into an unrecognized perturbed pathology in bvFTD, providing evidence in support of considerable lipid dysregulation in bvFTD.